Formulation and effect of a natural tendency face mask based on sodium alginate. - Rojas-Avalos, C.L.; Cabrera-Matías, F.; Campos-Arroyo, A.G. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
The trend for the consumption of natural cosmetic products for skin care is increasing, particularly those intended for the face and body. The classification of cosmetics is wide, as well as its specimens, whose organization depends on multiple factors, such as ingredients in the formulation, active compounds, function of the cosmetic, among others. Within natural cosmetics, whose ingredients must be natural or of natural origin, are hydro-plastic masks that are distinguished by the benefits they bring to skin care, in addition to their ingredients, among which are sodium alginate. The objective of the present work was to formulate and determine the effect of a natural tendency facial mask based on sodium alginate. The methodology used was quantitative experimental and three phases were carried out, which consisted of the design of the cosmetic powder formula, quality control tests and the elaboration of a sensory analysis. Among the results, the evaluation was obtained from a population of 60 panelists, 30 men and 30 women, which showed a positive correlation between the sensory attributes evaluated and the face mask, since no panelist established a negative correlation between the characteristics evaluated. The quality tests were successfully passed and high percentages of qualification were obtained in the sensory analysis, with the film-forming effect characteristic having the highest score, as it was perceived with 96.67% of the female panelists and 90% of the male panelists as "very pleasant", so a quality cosmetic formulation has been developed, with characteristics perceived as very pleasant to the people participating in the sensory study. In conclusion, it has been demonstrated that natural ingredients such as sodium alginate represent an alternative for the design of new formulations of facial masks with film-forming effect in the cosmetic industry.
Keywords: Sodium alginate; Quality control; Cosmetic; Hydroplastic mask